Cervical Ectopic Pregnancy with Placenta Percreta and Gross Hematuria: A Case Report - Malihe Hasanzadeh; Mohammad Ali Mohammadzadeh Rezaee; Golrokh Sherafati; Afrooz Azad; Masoumeh Mirtaymore (Mashhad University of Medical Sciences, 2016)
Background & aim: Cervical ectopic pregnancy is a rare variant of ectopic pregnancy, and placenta percreta is a complex and dangerous condition; patients with these conditions are difficult to manage. In this study, we present a rare case of placenta percreta in cervical pregnancy. Case report: A 32 -year-old woman with 19 weeks of gestation and gross hematuria was admitted to Qaem Hospital in February 2014. Abdominal sonography and magnetic resonance findings indicated percreta. Cystoscopy was performed, which demonstrated invasion of placenta into bladder mucosa. Surgery was planned due to severe hematuria, where cervical ectopic pregnancy with placenta percreta was found. Hysterectomy and partial cystectomy were performed, and to date, the patient is alive and healthy. Conclusion:Placenta percreta with bladder invasion can cause hematuria during pregnancy and early diagnosis can help with successful treatment and management of bleeding.